Indonesia Tidak Menganut Trias Politica - M, Mulyadi; Suhariyanto, Didik; H, Hartana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Trias Politica was first introduced by John Locke and then developed by Montesquieu. The Trias Politica concept functions to prevent power from one power which can give birth to authoritarian power. Trias Politica describes a balance of power, where power is divided into several regions to prevent arbitrary, bad power in terms of policy, law and politics. Indonesia is a legal and sovereign country, where there are Executive institutions such as the President and his ministers, Legislative institutions such as members of the People's Representative Council and Judicial Institutions such as the Judicial Commission, Constitutional Court and Supreme Court. With the existence of these institutions, Indonesia does not necessarily have pure Trias Politica, this can be seen from the perspective of legal politics that has developed so far. The aim of this research is to explain whether Indonesia adheres to the Trias Politica system purely or not. So in a conceptual way, legal politics can be seen clearly, even from a legal perspective it is clearly seen. Meanwhile, the public still views that Indonesia adheres to the Trias Politica system by only looking at the government institutions that have been established, without looking at the roles and functions as well as the authority of each institution. This means that research is very necessary for the development of state law in Indonesia. State law is a type of legal science that discusses the theory of the rule of law. Therefore, there is a connection with the Trias Politica Theory which was born from the thoughts of the English philosopher John Locke and then developed by Montesquieu.